2012
DOI: 10.1371/journal.pone.0044577
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Outbreak in Senegal in 2005: Was Climate a Factor?

Abstract: Cholera is an acute diarrheal illness caused by Vibrio cholerae and occurs as widespread epidemics in Africa. In 2005, there were 31,719 cholera cases, with 458 deaths in the Republic of Senegal. We retrospectively investigated the climate origin of the devastating floods in mid-August 2005, in the Dakar Region of Senegal and the subsequent outbreak of cholera along with the pattern of cholera outbreaks in three other regions of that country. We compared rainfall patterns between 2002 and 2005 and the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…Previous studies demonstrate statistically significant associations between infectious diseases and meteorological variations such as rainfall and temperature. The effects of climate change on the endemics of infectious diseases such as cholera, malaria, and plague have been recognized [11][20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrate statistically significant associations between infectious diseases and meteorological variations such as rainfall and temperature. The effects of climate change on the endemics of infectious diseases such as cholera, malaria, and plague have been recognized [11][20].…”
Section: Introductionmentioning
confidence: 99%
“…cholerae . Strains O1 and O139 can cause epidemic disease outbreaks, and studies from different regions around the world have correlated these to air and water temperature, rainfall, river discharge, and phytoplankton/zooplankton abundance and composition [ Colwell , ; Lobitz et al ., ; Rodó et al ., ; Gil et al ., ; Koelle et al ., ; Greer et al ., ; Constantin de Magny et al ., ]. Some analyses have suggested that climate change‐induced warming and eutrophication may exacerbate cholera outbreaks, with changing river flow patterns and flood events also potentially important [ Martinez‐Urtaza et al ., ; Tirado et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Constantin de Magny et al, 2012]. Some analyses have suggested that climate change-induced warming and eutrophication may exacerbate cholera outbreaks, with changing river flow patterns and flood events also potentially important Tirado et al, 2010].…”
Section: 1002/2017gh000089mentioning
confidence: 99%
“…Therefore, the current paper posits that understanding the environmental drivers and reservoirs of cholera, and the effectiveness of the prevention and control methods are critical for the eradication of cholera in SSA. This calls for a move beyond just epidemiology, to more cross-disciplinary research that includes comprehensive hydrology, environmental sciences, and climatic science studies, which are often overlooked in cholera investigations [16,17]. The current study draws largely from the recent cholera outbreaks in Zimbabwe to address three specific objectives: (1) to highlight the nature and dynamics of recent cholera outbreaks in SSA, (2) to discuss the importance of environmental drivers and reservoirs in controlling the dynamics of cholera outbreaks, and (3) to highlight future research directions and the need to harness emerging research tools to better understand the cholera dynamics.…”
Section: Introductionmentioning
confidence: 99%